2015
DOI: 10.1159/000440837
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of School Environment on Children's Respiratory Health

Abstract: Background/Aims: School indoor air quality is important because children spend most of their time outside home within the school environment. This study aimed to investigate the school environment and its impact on the respiratory health of the children. Methods: A total of 191 pupils in the 9- to 11-year age group were selected from 5 primary state schools. Validated school and health questionnaires, spirometry, acoustic rhinometry, nasal lavage, urine for environmental tobacco smoke biomarkers and traffic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…These results were in accordance with some previous studies in the literature, namely with a study in primary school children (aged 9-11 years old) from Malta that also reported a direct association between wheezing and high exposure to indoor formaldehyde and PM 2.5 [26]. Rawi et al [10] stated significant associations between wheezing and indoor PM 2.5 concentrations in preschools (aged 5-6 years old) from Selangor, Malaysia and no significant association between indoor CO 2 concentration and respiratory symptoms.…”
Section: Modelling Associations Between Iap Exposure and Active Wheezingsupporting
confidence: 93%
“…These results were in accordance with some previous studies in the literature, namely with a study in primary school children (aged 9-11 years old) from Malta that also reported a direct association between wheezing and high exposure to indoor formaldehyde and PM 2.5 [26]. Rawi et al [10] stated significant associations between wheezing and indoor PM 2.5 concentrations in preschools (aged 5-6 years old) from Selangor, Malaysia and no significant association between indoor CO 2 concentration and respiratory symptoms.…”
Section: Modelling Associations Between Iap Exposure and Active Wheezingsupporting
confidence: 93%
“…The mean indoor PM 2.5 level of 17.78 μg/m 3 and CO (9.11 ppm) exceeded the thresholds set by the WHO. 59 The Park study showed the effects of outdoor temperature on the exam day on student performance, using 4.6 million high school exit tests in New York. The author finds that students taking an exam on a day with temperatures higher than 32°C scores up to 14% lower.…”
Section: Air Quality Guidelines (Aqg)mentioning
confidence: 99%
“…In general, children spend more time in schools than in any other indoor environment excluding homes (i.e. most of daytime and up to 30% of their time), and thus, schools can contribute significantly to children's daily exposure to air pollution (Fsadni et al 2018;Branco et al 2020). IAQ in schools depends on many factors including ventilation efficiency, frequency of cleaning and number of students in the classroom (Madureira et al 2018).…”
Section: Introductionmentioning
confidence: 99%